2012
DOI: 10.1038/ncomms2247
|View full text |Cite
|
Sign up to set email alerts
|

Water tribology on graphene

Abstract: Classical experiments show that the force required to slide liquid drops on surfaces increases with the resting time of the drop, t rest , and reaches a plateau typically after several minutes. Here we use the centrifugal adhesion balance to show that the lateral force required to slide a water drop on a graphene surface is practically invariant with t rest . In addition, the drop's three-phase contact line adopts a peculiar micrometric serrated form. These observations agree well with current theories that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 28 publications
1
79
0
Order By: Relevance
“…However, the method suffers from the inability to control the normal and lateral forces independently. This is a major drawback because the relationship between these forces can be non-trivial 30,31 . A centrifugal adhesion balance can overcome the force coupling problem, but is more suitable for quasi-static measurements (for example, to study the lateral force required to unpin a droplet) than for dynamic measurements (for example, to investigate energy dissipation and the corresponding dissipative forces as a function of droplet speed).…”
mentioning
confidence: 99%
“…However, the method suffers from the inability to control the normal and lateral forces independently. This is a major drawback because the relationship between these forces can be non-trivial 30,31 . A centrifugal adhesion balance can overcome the force coupling problem, but is more suitable for quasi-static measurements (for example, to study the lateral force required to unpin a droplet) than for dynamic measurements (for example, to investigate energy dissipation and the corresponding dissipative forces as a function of droplet speed).…”
mentioning
confidence: 99%
“…The wear rate of Fig. 12 Effect of time on drop retention force for various systems ((a) and (b)) and image of water drops on graphene (c) [85]. PTFE is reduced by four orders of magnitude due to graphene additives according to a report by Kandanur et al [95].…”
Section: Applicationsmentioning
confidence: 94%
“…A detailed analysis of the molecular structure attributed this result to strain-induced change in the interfacial potential energy barrier and the commensurate structure between the graphene walls and the first water layer. In addition to theoretical works, a pioneering experiment done by N'guessan et al probed water tribology on graphene [85]. They found that the lateral force required to slide a water drop on a graphene surface is independent of the resting time of the drop, contrary to classical experiments (Fig.…”
Section: Frictional Interaction Between Liquid and 2d Materialsmentioning
confidence: 99%
“…In our group it has been reported that placing micro sized sessile water ''satellite drops'' around a central water drop produces effective evaporation suppression of the central drop [38,39], nevertheless, a detailed study on this effect is performed here for the first time.…”
Section: Introductionmentioning
confidence: 94%